Profiling of genetic variants of bovine κ-casein macropeptide by electrophoretic and chromatographic techniques - Coolbear, Kate P.; Elgar, David F.; Ayers, John S. (International dairy journal, 1996)
Bovine κ-caseins of single variant phenotype (AA and BB) and mixed phenotype (AA, BB and AB) were purified from milk and the corresponding κ-casein macropeptides prepared by chymosin hydrolysis. The macropeptides were characterized by PAGE, Mono Q- and reverse-phase HPLC. Chromatographic profiles showed marked differences between the monovariant macropeptides, attributable to differences in glycosylation. The B variant macropeptide was found to be more highly glycosylated than the A variant with an apparently greater number of oligo-saccharide chains per peptide unit and a higher level of sialylation. The analytical profiles for the mixed variant sample were a composite of those for the individual variants, all components being accounted for by one or other variant. It was concluded that while the overall extent of glycosylation may vary, there are consistent patterns of glycosylation for each variant.